Variable Speed Drive of Single Phase Induction Motor Using Frequency Control Method - Aung Zaw Latt; Ni Ni Win (2009 International Conference on Education Technology and Computer, 2009)
Single-phase induction motors are widely used in home appliances and industrial control. The multispeed operation and multipurpose operation are provided by controlling the speed of these motors. This research paper is variable speed drive of induction motor using frequency control method. It is to develop the solid state control system to be reliable and economically feasible to use with fractional horse power motors. The proposed variable speed drive includes power conversion section (AC to DC and DC to AC), used the switching element of IRF 840 N-channel MOSFET. The four IRF 840 MOSFETS are used as H-bridge inverter to provide the alternating current to the motor. In this drive, C124 transistors and MJE 13002 transistors are used as driver circuit to drive the H-bridge inverter. There are two power supplies in this drive. The 12 V power supply is used for frequency control circuit and driver circuit. The 300 V power supply is used for H-bridge inverter. In this drive, pulse width modulation SG3525A IC is used to control the frequency. The frequency range of the constructed variable drive circuit is 16 Hz to 56 Hz at constant voltage for changing the speed of induction motor. In this research paper, drive schemes of single-phase induction motor, principle operations of components used in constructed variable speed drive, and design calculation to construct this drive are included. Moreover, the experimental tests of this drive when driving a fractional horse power single-phase induction motor are described.